If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + 5 = 2y + 7 Reorder the terms: 5 + 3y = 2y + 7 Reorder the terms: 5 + 3y = 7 + 2y Solving 5 + 3y = 7 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 5 + 3y + -2y = 7 + 2y + -2y Combine like terms: 3y + -2y = 1y 5 + 1y = 7 + 2y + -2y Combine like terms: 2y + -2y = 0 5 + 1y = 7 + 0 5 + 1y = 7 Add '-5' to each side of the equation. 5 + -5 + 1y = 7 + -5 Combine like terms: 5 + -5 = 0 0 + 1y = 7 + -5 1y = 7 + -5 Combine like terms: 7 + -5 = 2 1y = 2 Divide each side by '1'. y = 2 Simplifying y = 2
| (4y^2-7y-1)-(-2y^2+7y+4)+(6y^2-9y-9)=0 | | 6/7+4/5= | | 72=3x | | 85a=9435 | | (3x-7)-5=-3 | | 4473=213k | | 0.7(6-0.3n)=-21 | | 2904=33z | | y=x^3-9x^2+18x | | 39y=663 | | 64a=2048 | | Y=x^3+4x^2-12x | | 1275=51b | | 9x-258=3x | | 9x-21=5x+10 | | 27c=945 | | 248=31e | | 14-21=10 | | 9z-19-2z+5=0 | | 2x+5x-3x= | | 43a+10-26a=26 | | 11z=385 | | -5y-5=4y-6 | | 6x-6y=86 | | 32b=288 | | 9-(2x-5)=7-3x | | 16y=128 | | e^3x+7=16 | | 7.75(h)+20=80 | | 6(x-5)=5(x-5) | | 22371973281+2198312878317892121441322= | | 54=6a |